KOMUNIKASI POLITIK MUBALLIG DI KOTA PALU (Studi Kampanye Pemilihan Presiden dan Wakil Presiden 2014) - Syamsuri Syamsuri (INFERENSI: Jurnal Penelitian Sosial Keagamaan, 2015)
This study revealed the phenomenon of mubaligh involvement in political events of the Election of President and Vice President of the Republic of Indonesia, the period from 2014 to 2019. The study took place during the campaign, from the date of June 4, 2014 to July 5, 2014. Through a phenomenology approach, mubaligh in Palu attempted to negotiate among stakeholders power of political parties, relate consolidation among voters, and the description of imaging as political messages to Muslim audiences. Various missionary activities always were used to convey the vision and mission of Candidates for President and Vice President whom they supported. The largest Muslim women organization in Palu, Alkhairaat, together with mubaligh, participated in the political contest